Development of thiazole-appended novel hydrazones as a new class of α-amylase inhibitors with anticancer assets: an in silico and in vitro approach. Issue 4 (17th March 2023) - Chahal, Sandhya; Punia, Jyoti; Rani, Payal; Singh, Rajvir; Mayank; Kumar, Parvin; Kataria, Ramesh; Joshi, Gaurav; Sindhu, Jayant
Abstract : Thiazole-clubbed hydrazones exhibited in vitro α-amylase inhibitory response in the range of IC50 values from 0.23 ± 0.003 to 0.5 ± 0.0 μM. 5b was found to be the least cytotoxic and most potent α-amylase inhibitor. Abstract : Hyperamylasemia is reported to be associated with numerous chronic diseases, including diabetes and cancer. Considering this fact, we developed a series of thiazole-clubbed hydrazones. The derivatives were explored for their in vitro α-amylase inhibitory activity, which was further corroborated with their anticancer assets using a panel of cancer cells, including colon cancer (HCT-116), lung cancer (A549), and breast cancer (MDA-MB-231). To better understand pharmacokinetics, the synthetic derivatives were subjected to in silico ADMET prediction. The in vitro based biological investigation revealed that compared to the reference drug acarbose (IC50 = 0.21 ± 0.008 μM), all the synthesized compounds (5a–5aa ) exhibited in vitro α-amylase inhibitory response in the range of IC50 values from 0.23 ± 0.003 to 0.5 ± 0.0 μM. Along with this, the proliferations of the HCT-116, A549 and MDA-MB-231 cells were inhibited when treated with the synthesized compounds. Notable cancer cell growth inhibition was observed for compounds 5e, 5f and 5y, which correlated with their α-amylase inhibition. Additionally, the kinetics investigation revealed that 5b, 5e, 5f and 5y exhibit uncompetitive inhibition. 5b was found to be the least cytotoxic and most potent α-amylase inhibitor and was further validated by absorption and fluorescence quenching technique.